PERTUMBUHAN DAN HASIL DUA VARIETAS KEDELAI (Glycine max L. Merril) PADA PERBEDAAN PUPUK ORGANIK (Growth and Yield of Two Soybean (Glycine max L. Merill) Varieties at Different Organic Fertilizers) - Nyimas Myrna E. Fathia; Budiyati S. Ichwan; Helmi Salim (Bioplantae, 2013)
This Research was conducted at Teaching and Research Farm , Faculty of Agriculture, Jambi University started from July 2013 untill October 2013. Experiment was arranged in a Randomized block design with factorial treatment and three replication. First factor was variety consist of two level Anjasmoro and Grobogan . Second factor was different organic fertilizer cattle manure, chicken manure, goat manure, and Cities Compost Trash. Variables observed were plant height (cm), plant dry weight (g), number of filled pod, number of pod per plant, 100 seed weight (g), and seed weight per plant (g). Data were analysed using analisys of variance and continued with DNMRT test with 5 % level of significance. Results showed that there were not different effect of organic manure applied on both soybean varieties. At the other hand, application of organic manures had significant effect on number of filled pod, number of pod per plant, plant dry weight, and seed weight per plant. Meanwhile, there were sicnificant effect between two soybean varieties and Cities Compost Trash on number of filled pod, number of pod per plant, plant dry weight and seed weight per plant. Keyword : soybean, organic, manure, variety